GESTALT AKUNTANSI : KOMITMEN PERUSAHAAN DALAM PENGUNGKAPAN INTELLECTUAL CAPITAL - Pratama, Aditya; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
Intellectual capital disclosure is a tool that can be used by a company to communicate withtheir stakeholders. With disclose company intellectual information, a company could decreaseasymmetric information level with their stakeholders. The nature of intellectual capital disclosureis voluntary disclosure, therefore, a company had choose to not disclose some information if theirfelt it will not bring an advantage for them. The purpose of this research is to compare intellectualcapital disclosure in the prospectus with the intellectual capital disclosure in the subsequentannual report. The main objective was to investigate a company commitment toward intellectualcapital disclosure. A higher level of disclosure on annual report showed a company commitmenttoward intellectual capital disclosure. The second objective was to investigate whether companiesreport more on intellectual capital in the prospectus rather than in annual report.This study was a quantitative study using secondary data, namely a company prospectusand subsequent annual report which collected from www.idx.co.id also pojok BEI UNDIP. Numberof used were as many as 38 different companies, which IPO from 2005-2010 in four differentcategory industry, which banking, manufactured, services, and property. 47 item of intellectualcapital disclosure measured using content analysis method. SPSS version 17.0 was used toprocessing data through multiple linier regressions.The result of hypothesis test showed the existence of intellectual capital disclosurecommitment was not confirmed. Moreover, the results showed that companies report moreextensively on intellectual capital in their prospectus rather than their annual report.